(untitled) (Ius Novum, 2023)
The subject of this article’s interest is the regulation of Art. 62 sec. 1 of the Act on Counteracting Drug Addiction of July 29, 2005, often called in the literature as consumer possession. The basic problem related to the subject matter indicated in the title is related to the definition of the legal interest in Art. 62 sec. 1 of the act. Contrary to appearances, its indication is not a simple or unequivocal matter, as there may be doubts as to whether such a good protected by law exists and, if so, whether it should be protected under criminal law. The article also indicates the correlation of this legal good and the need to protect it with other legal goods protected by the Constitution (e.g., individual freedom). Finally, the article also defines the significance of the consent of the possessor of a given good for the exclusion of unlawfulness or the absence of any attack on the legal good. Behavior taken with the consent of the owner, allegedly “violating” the legal interest, is after all an act that is consistent with the norm from the very beginning, and therefore there is no element of unlawfulness in it. As such, it is not a criminal act. There can be doubts whether in the case of possession and use of drugs, there is a threat to the legal good, or whether it is a behavior that from the very beginning, due to the consumer’s consent, is legal behavior. The article is critical of the existing criminal law regulations, and its clue is the thesis about the exclusively medical and social, not criminal law, problem of drug addiction.